RANCANG BANGUN MODEL KELEMBAGAAN AGRIBISNIS PADI ORGANIK DALAM MENDUKUNG KETAHANAN PANGAN - Kusnandar, Kusnandar; Padmaningrum, Dwiningtyas; Rahayu, Wiwit; Wibowo, Agung (Universitas Muhammdaiyah Surakarta, 2013)
The aim of this research was to design an institutional model for organic rice agribusiness. Data were collected through interviews and focus group discussion which includes the primary and secondary data. Data analysis methods for organic rice agribusiness institutional development were: system analysis, institutional analysis and interactive analysis. Result of the research indicated that organic rice agribusiness system in Sragen was supported by a strong superstructures. There were Go Organic 2010 program and many policies of Sragen government includes: cultivation, extension, marketing, and certification. Profile community of organic rice agribusiness includes organic rice farmers, farmer groups, associations of farmer groups (gapoktan), extension agents, organic rice farmer associations, organic rice agro-industry companies, government, and consumers. Designing models with the agribusiness system suggested a cluster of industry (industrial cluster) which composed of five subsystems, namely: upstream agribusiness, on farm agribusiness, down stream agribusiness, supporting agribusiness system, and marketing subsystem.